Haptic information provided by the anchor system reduces trunk sway acceleration in the frontal plane during tandem walking in older adults - Silva Costa, Andreia Abud da; Rossi Manciopi, Priscila Abbari; Mauerberg-deCastro, Eliane [UNESP]; Moraes, Renato (Elsevier B.V., 2015)
This study assessed whether the use of an anchor system benefited older adults who performed a tandem walking task. Additionally, we tested the effects of practice with the anchor system during walking on trunk stability, in the frontal plane, of older adults. Forty-four older adults were randomly assigned to three groups: control group, 0 g anchor group, and 125 g anchor group. Individuals in each group performed a tandem walking task on the GaitRite system with an accelerometer placed on the cervical region. The participants in the 125 g anchor group held, in each hand, a flexible cable with a light mass attached at the end of the cable, which rested on the ground. While the participants walked, they pulled on the cables just enough to keep them taut as the masses slid over the ground. The 0 g anchor group held an anchor tool without any mass attached to the end portion. The results of this study demonstrated that the use of the anchor system contributed to the reduction of trunk acceleration in the frontal plane. However, this effect did not persist after removal of the anchors, which suggests that the amount of practice with this tool was insufficient to generate any lasting effect, or that the task was not sufficiently challenging, or both. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Gait patterns; Older adults; Haptic information; Anchor system